"The right to food is nature too": food justice and everyday environmental expertise in the Salvadoran permaculture movement. Issue 6 (3rd June 2017) - Millner, Naomi
ABSTRACT: In El Salvador a growing permaculture movement attunes small-scale farming activities to principles of ecological observation. The premise is twofold: close-grained appreciation of already-interacting biophysical processes allows for the design of complementary social and agricultural systems requiring minimum energy inputs. Secondly, the insistence on campesino smallholders as actors in the design of sustainable food systems directly addresses decades of "top-down" developmental interventions, from Green Revolution experiments in the 1960s and 1970s to international food security programmes in the 1990s. Permaculture connects food insecurity to the delegitimisation of smallholder innovation and insists that, through sharing simple techniques, campesino farmers can contribute towards future-oriented questions of environmental sustainability. This repositioning is brought about through the mobilisation of pedagogical techniques that legitimise the experiences and expertise of small-scale farmers, while standardising experimental methods for testing, evaluating and sharing agroecological practices. Like food sovereignty and food justice movements, Salvadoran permaculture links hunger with longer histories of (uneven) capital accumulation and dispossession and renders campesino farmers its protagonists. By modelling a form of expertise premised in intimate involvement with specific environments, permaculture goes still further, seeking to dislodge a pervasive knowledge politics that situates some as knowers and innovators, and others as passive recipients. This grounds human rights in an ethos of caring for the "more-than-human" world and places emphasis on a corollary right as part of food justice, increasingly being demanded "from below": the right to know.